Preliminary achievement of molecular taxonomy of some important animal groups in Vietnam - Chau, Nguyen Ngoc; Long, Phan Ke; Phap, Trinh Quang; The, Dang Tat (Academia Journal of Biology, 2014)
The molecular taxonomy in Vietnam has been started since year 2000. In the beginning stage a numerous molecular techniques such as PCR, PCR-RFLP, and sequencing has been applied for taxonomy of some important animals and plant in Vietnam. To date the molecular characters of 51 indigenous animal species and subspecies has been characterized. Based on these molecular data some about twenty new species to science were revealed. Among them, four new species of plant parasitic nematodes (Radopholus spp. and Apratylenchus spp.), eleven new species of enthomopathogenic nematodes (Steinernema spp. and Heterorhabditis spp.) and one species of pulmonary trematodes (Paragonimus vietnamensis). The phylogenetic tree constructed from generic data has allowed to clarify some unclear and confusion situation on taxonomic of some species as well as subspecies of primates (Rhinopithecus avunculus, Pygathrix nemaeus subspp., P. nigripes, Trachypithecus germaini, T. barbei holotephreus, T. hatinhensis, T. delacouri, T. francoisi subspp. and T. barbei subsp), swallow (Aerodramus fuciphagus), earth worm (Pheretina spp.), forest hare (Lepus sinensis), grey civet (Paguma spp.) and Indian cobra (Naja spp.). The phylogenetic trees produced based on maximum parasimony and maximum likelihood analyses were allowed to clarify and revise with the interpretation of the taxonomic position and origin some indigenous plant parasitic and enthomopathogenic nematodes in Vietnam. In addition, the molecular techniques has also been assembled molecular proofs for preventing illegal trade of animals and plants belonging to CITES convention. The paper also been affirmed the advantage of molecular techniques that are not only as useful tools for taxonomy but they are also very real measure for phylogenic inference. Subsequently, the necessary of molecular approach in taxonomy and phylogeny as well as biological conservation of animals and plants in Vietnam was discussed in the paper.